3, 6‐Diaminocarbazole doped fluorescent electrospun nanofibers for highly sensitive detection of nitroaromatics. Issue 28 (9th May 2022) - Kumar, Anshu; Kumar, Vishal; Nath, Prathul; Satapathi, Soumitra
Abstract: Electrospinning is an efficient technique to fabricate nanofibers of controlled diameter and uniform morphology. Herein, we report a low‐cost and high‐yield route to fabricate PAN/DAC composite nanofibers and its use for vapor sensing of 2, 4‐Dinitrotoluene (DNT) and 2, 4, 6‐Trinitrotoluene (TNT) with a detection level in the range of parts‐per‐billion. Furthermore, the sensing ability and photo‐induced electron transfer mechanism of DAC towards DNT and TNT in the solution phase were also investigated in detail via absorption, steady‐state, and time‐resolved fluorescence spectroscopy and further supported by density function theory (DFT). The calculated Stern‐Volmer quenching constants, 810 M −1 (DNT) and 1170 M −1 (TNT), revealed that DAC is not much sensitive in solution‐phase because of the self‐condensation phenomenon of DAC molecules. This concern was addressed by the development of a fluorescent nanofiber probe constituting π‐electron‐rich carbazole (CZ) derivatives, namely 3, 6‐Diaminocarbazole (DAC) as a fluorescent material and polyacrylonitrile (PAN) as a support polymatrix. This fluorophore‐doped nanofiber matrix was fabricated at a relatively lower wt% ratio (PAN:DAC::10:6), obtaining an average diameter of 857 nm and exhibited promising features in the vapor detection of DNT and TNT such as fast response time, excellent sensitivity and selectivity. Reduction of self‐condensation caused DAC molecules' fluorescence self‐quenching by simply employing the electrospinning technique to cast PAN/DAC nanofibrous film. This work promises a new aspect of sensitivity enhancement of carbazole molecular unit by amine modification and further incorporation into the polymer matrix. This nanofiber‐based sensor can lead to the design and development of highly efficient and field‐deployable vapor sensors for the detection of nitroaromatic compounds, with application in both explosive sensing and environment pollution. Abstract : A low‐cost and high‐yield route to fabricate Polyacrylonitrile/3, 6‐Diaminocarbazole (PAN/DAC) composite nanofibers and its use for vapor sensing of 2, 4‐Dinitrotoluene and 2, 4, 6‐Trinitrotoluene at a lower range of parts‐per‐billion level. This nanofiber sensing probe consists of a fluorescent π‐electron rich carbazole (CZ) derivatives, namely DAC as sensor probe and PAN as support polymer matrix. This study delivered a new aspect of sensitivity enhancement of carbazole molecular unit by amine modification and further incorporation into the polymer matrix.